การประเมินสภาวะสบายตาจากค่าความส่องสว่างและอุณหภูมิสีจากโคมฟลูออเรสเซนต์ - ณวรา นราราษฎร์ (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
This Research has as its objective the study of the appropriate illuminance for reading and for using the computer, which are common activities in office buildings, with the use of task-ambient lighting, and to fine appropriate correlated color temperature of the fluorescent lamps that provides visual comfort, conserves energy, and uses energy effectively. The research data was gathered by way of a questionnaire following the experimental patterns in the study. The questionnaire respondents were put into two types based on their activities in the office: those with paper tasks and those with computer tasks. Each group would complete the tests with different levels of illuminance. A total number of 240 people took part in the tests, which incorporated three types of light sources: ceiling lights, personal lights, and ceiling and personal lights. The color temperatures of the fluorescent lamps used in the experiments were warm white (3000 K) and cool white (40000 K). According to the study, it was found that in the case of paper tasks at an illuminance of 100-500, ceiling lights provided a higher level of visual comfort than personal lights. However, at the illuminance of 700-900 lux, personal lights provided a higher level of visual comfort. In the case where both ceiling and personal lights were used, which provided task-ambient lighting, the illuminance required was lowest as a variety of illuminance could be achieved. The lights could be adjusted to fit an individual s specific needs. Regarding the color temperature, cool white was found to give more satisfaction in terms of visual comfort than warm white. In addition, in comparing the average illuminance required for paper tasks and computer tasks, it was found that paper tasks need higher illuminance than computer tasks. The research results are highly beneficial in the application of task-ambient lighting was useful as it could reduce the energy consumption in the building and the use of color temperature of fluorescent lamps appropriate to the tasks and providing optimal visual comfort.